Studi Pengembangan Komposit Al/Al2O3 Berpori dengan Space Holder Latex terhadap Sifat Mekanik dan Fisik - Gunawan, Gunawan; Sofyana, Reni; Arifin, Amir (Jurnal Rekayasa Mesin, 2022)
Composite materials are combinations of multiple or more ingredients that have different materials used for materials and materials that have pores produced from space holder material. This study aims to identify aluminum metal as aluminum metal (aluminum metal foam) to the mechanical properties and physical properties (density and porosity) with the same temperature and holding time. Fabrication method is powder metallurgy, with compacting of 100 kg/cm2 and using a sintering temperature of 5000C with a holding time of 2 hours. Tests and observations made were Thermo Graviemetric Analysis (TGA) to determine the process of decreasing space space holder, X-Ray Diffraction (XRD) to characterize crystalline phases formed, test Density, Scanning Electron Microscopy (SEM).